"Enteroatmospheric Fistulae"—Gastrointestinal Openings in the Open Abdomen: A Review and Recent Proposal of a Surgical Technique. (June 2013) - Marinis, A.; Gkiokas, G.; Argyra, E.; Fragulidis, G.; Polymeneas, G.; Voros, D.
The occurrence of an enteric fistula in the middle of an open abdomen is called an enteroatmospheric fistula, which is the most challenging and feared complication for a surgeon to deal with. It is in fact not a true fistula because it neither has a fistula tract nor is covered by a well-vascularized tissue. The mortality of enteroatmospheric fistulae was as high as 70% in past decades but is currently approximately 40% due to advanced modern intensive care and improved surgical techniques. Management of patients with an open abdomen and an enteroatmospheric fistula is very challenging. Intensive care support of organs and systems is vital in order to manage the severely septic patient and the associated multiple organ failure syndrome. Many of the principles applied to classic enterocutaneous fistulae are used as well. Control of enteric spillage, attempts to seal the fistula, and techniques of peritoneal access for excision of the involved loop are reviewed in this report. Additionally, we describe our recent proposal of a lateral surgical approach via the circumference of the open abdomen in order to avoid the hostile and granulated surface of the abdominal trauma, which is adhered to the intraperitoneal organs.